2008
DOI: 10.1080/00016340802268880
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization in pregnancy during the years 1992–2005 in the central west region of Sweden

Abstract: Anti-D still accounts for the most severe immunizations and for most of the cases where ET was necessary. Low-risk invasive techniques to evaluate and treat pregnancies complicated by alloimmunization seem possible and accurate, avoiding invasive procedures that may exacerbate the immunization during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 15 publications
11
46
1
1
Order By: Relevance
“…A wide variation from 0.9 to 7.1 % can be seen regarding alloimmunization rates in the D antigen-negative group [8,10,17]. The rate of alloimmunization in the D antigen-negative group is higher in present study.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…A wide variation from 0.9 to 7.1 % can be seen regarding alloimmunization rates in the D antigen-negative group [8,10,17]. The rate of alloimmunization in the D antigen-negative group is higher in present study.…”
Section: Discussionmentioning
confidence: 42%
“…Pahuja et al [6] detected in 78.43 %, Gottvall and Filbey [10] found in 60 % of cases. Howard et al [15] and Filbey et al [16] found that anti-D was responsible for 41 and 45.6 % and it was the leading offender despite immunoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better knowledge of the molecular biology of the immune process and better communication between gynecologists and transfusion specialists has significantly improved immunoprophylaxis among pregnant women in the area we cover in the last 10 years. However, besides the D antigen, other blood group antigens of the Rh system (C, c, E, e) and other blood group systems (Kell system) have come to light in Europe [11,12] and in our region. Of the 384 sensitized pregnant women in our study, the non-RhD antibody was present in 228 women, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal red blood cell alloimmunization is an important cause of morbidity and mortality in the antepartum and neonatal periods with the frequency found to range from 0.4% to 2.7% worldwide [1][2][3][4][5]. Maternal red blood cell alloimmunization causes fetal-neonatal anemia with ebral artery Doppler evaluation.…”
Section: Introductionmentioning
confidence: 99%